Three species of hackled-orb web spider genus Miagrammopes from China (Araneae, Uloboridae) - Liang, Yun; Cai, Qu; Liu, Jinxin; Yin, Haiqiang; Xu, Xiang (Zootaxa, 2021)
Three species of the genus Miagrammopes O. Pickard-Cambridge, 1870 are described from China, including two new species, M. rutundus Liang & Xu, n. sp. from Guangxi Zhuang Autonomous Region and M. auriculatus Cai & Xu, n. sp. from Tibet Autonomous Region, and one known species, M. bifurcatus Dong, Yan, Zhu & Song, 2004. The female of M. bifurcatus is described for the first time. Both detailed illustration and a distribution map of the three species are provided.